Daring Darleen, queen of the screen - Nesbet, Anne (Candlewick Press, 2022)
It's 1914 and twelve-year-old Darleen Daring is a silent film star. When a fake kidnapping set up by her studio goes wrong, Darleen finds herself in the hands of actual criminals who have also just kidnapped Victorine Berryman, the heiress of one of America's largest fortunes. Darleen and Victorine will have to live their own adventure serial, with dramatic escapes, murder plots, and a runaway air balloon in order to survive.